PERAN PTPN VII DALAM PEMBERDAYAAN HOME INDUSTRI KERIPIK PISANG (Studi Pada Home Industri Keripik Pisang Mitra Binaan PTPN VII Lampung) - Armelia, Gita Rosalita; Damayantie, Anita (SOCIOLOGIE, 2013)
The concept of empowerment (rural communities) can also be understood in two ways glance. First, empowerment is interpreted in the context of society stand to position. Position is not the object of the beneficiary communities that depend on grants from external parties such as the government, except in the position as the subject of doing independently. PTPN VII as part of the ruling element also has a program of community empowerment is one of them and build partnerships within the program, this program will help the management of banana chips home industry in their efforts to expand. PTPN VII partnership program has a vision capable of creating and supporting sustainability through harmonization of the interests of enterprises, community social relationships, and environment. Partnerships program be good partnership activities in the field of construction or gardening efforts through the provision of capital construction management and outreach efforts. Formulation of the problem in this research is how PTPN VII role in the development of home industry Lampung banana chips. Type of research used in this study is qualitative by profound interview method. Based on the results of research and discussion that the author did then obtained conclusion is, the assistance provided by PTPN VII of the building as process partners to develop joint communities who want to expand their efforts.Keywords: Empowerment, communities